Thioflavin T fluoresces as excimer in highly concentrated aqueous solutions and as monomer being incorporated in amyloid fibrils - Anna I. Sulatskaya (Nature Portfolio, 2017)
Abstract Fluorescence of thioflavin T (ThT) is a proven tool for amyloid fibrils study. The correct model of ThT binding to fibrils is crucial to clarify amyloid fibrils structure and mechanism of their formation. Although there are convincing evidences that ThT has molecular rotor nature, implying it’s binding to fibrils in monomer form, speculations concerning ThT binding to fibrils in aggregated forms appear in literature so far. The elaborated approach for fluorescence intensity correction on the inner filter effects applied to ThT aqueous solutions with a wide range of concentration allowed characterizing ThT excimers fluorescence and showing its difference from that of ThT bound to fibrils. Obtained results experimentally prove the monomer model of ThT binding to amyloid fibrils and demonstrate wide capacity of the used approach in the spectroscopy of other fluorescent dyes for examination of concentration self-quenching and deformation of fluorescence spectra, dye molecules interaction, dimers and excimers formation.